2018
DOI: 10.4103/ejd.ejd_54_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of apical constriction position in incisor and molar teeth: An in vitro study

Abstract: Objective:The apical constriction (AC) and the apical foramen (AF) are the principal reference points used to determine the apical limit for instrumentation and root canal filling. AC varies in different races, and the aim of the current study was to measure and compare the distances from AC to AF and the anatomical apex (AA) in incisor and molar teeth in the Iranian population.Materials and Methods:Forty-five roots of incisor teeth and 45 roots of molar teeth were selected randomly in Isfahan Province, Iran. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In Wolf's study (15), the mean distances between AC and AA were 0.82mm (MB), 0.81mm (DB) and 1.02mm (P) in maxillary first molars, 0.54mm (MB), 0.43mm (DB) and 0.63mm (P) in maxillary second molars. In Mousavi's study under microscopic, the mean distance between AC and AF was 0.85 ± 0.33 mm in incisors, and the mean distance between AC and AA was 1.23 ± 0.39 mm in incisors (34). By the use of microscopic Kutter and Dummer found that the narrowest part of the canal was 0.59 mm to AF (17) or 0.89 mm to AA on average (32).…”
Section: Discussionmentioning
confidence: 92%
“…In Wolf's study (15), the mean distances between AC and AA were 0.82mm (MB), 0.81mm (DB) and 1.02mm (P) in maxillary first molars, 0.54mm (MB), 0.43mm (DB) and 0.63mm (P) in maxillary second molars. In Mousavi's study under microscopic, the mean distance between AC and AF was 0.85 ± 0.33 mm in incisors, and the mean distance between AC and AA was 1.23 ± 0.39 mm in incisors (34). By the use of microscopic Kutter and Dummer found that the narrowest part of the canal was 0.59 mm to AF (17) or 0.89 mm to AA on average (32).…”
Section: Discussionmentioning
confidence: 92%
“…In Wolf’s study [ 14 ], the mean distances between AC and AA were 0.82 mm (MB), 0.81 mm (DB) and 1.02 mm (P) in maxillary first molars, 0.54 mm (MB), 0.43 mm (DB) and 0.63 mm (P) in maxillary second molars. In Mousavi’s study under microscopic, the mean distance between AC and AF was 0.85 ± 0.33 mm in incisors, and the mean distance between AC and AA was 1.23 ± 0.39 mm in incisors [ 33 ]. By the use of microscopic Kutter and Dummer found that the narrowest part of the canal was 0.59 mm to AF [ 16 ] or 0.89 mm to AA on average [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the research of Ngan Duong Hoang, Van Dinh Thi Khanh and Khoa Pham Van (2013) [7] about the rate of apical foramens deviating from the apex, our research was higher, reporting a 47.76% of cases that have deviations from the apex. According to the research of Mousavi, S. A. et al (2018) [6], apical foramen position is 0.847 ± 0.33 mm from apex at anterior teeth and 0.709 ± 0.27 mm at posterior teeth. Based on this result, dentists when performing endodontic treatments may form ideas about positions of apical foramens so that they can explore instruments into the root canals with right directions.…”
Section: Locations Of the Apical Foramenmentioning
confidence: 97%